2012
DOI: 10.1029/2011gl050242
|View full text |Cite
|
Sign up to set email alerts
|

Low‐energy ions: A previously hidden solar system particle population

Abstract: [1] Ions with energies less than tens of eV originate from the Terrestrial ionosphere and from several planets and moons in the solar system. The low energy indicates the origin of the plasma but also severely complicates detection of the positive ions onboard sunlit spacecraft at higher altitudes, which often become positively charged to several tens of Volts. We discuss some methods to observe low-energy ions, including a recently developed technique based on the detection of the wake behind a charged spacec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(201 citation statements)
references
References 63 publications
11
190
0
Order By: Relevance
“…However, a recently developed technique, based on the observation of the wake formed behind the charged spacecraft by the supersonic flow of the low-energy ions, allows the detection of these populations (Engwall et al, 2006(Engwall et al, , 2009). An analysis by André and Cully (2012) of the Cluster dayside data, using this technique, showed that the lowenergy ions can dominate 50-70 % of the time the region inside of the magnetopause, even at sectors where no plasmaspheric plumes are observed. This provides additional evidence for the plasmaspheric wind.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recently developed technique, based on the observation of the wake formed behind the charged spacecraft by the supersonic flow of the low-energy ions, allows the detection of these populations (Engwall et al, 2006(Engwall et al, , 2009). An analysis by André and Cully (2012) of the Cluster dayside data, using this technique, showed that the lowenergy ions can dominate 50-70 % of the time the region inside of the magnetopause, even at sectors where no plasmaspheric plumes are observed. This provides additional evidence for the plasmaspheric wind.…”
Section: Discussionmentioning
confidence: 99%
“…Since ions are seen to migrate across field lines on all the terrestrial planets -through the plasmaspheric wind and plumes at Earth (Lemaire & Schunk 1992;André & Cully 2012) Edberg et al 2011) -and, on average, escape is unhindered by the magnetic field, we treat cross-field ion loss as one single process, although the microphysical processes behind it are likely to be different at the different planets.…”
Section: Escape Processesmentioning
confidence: 99%
“…Cross-field ion loss includes the plasmaspheric wind and plumes on magnetised planets (Lemaire & Schunk 1992;André & Cully 2012) and ions being lost directly from the ionosphere at the unmagnetised planets (Lundin et al 2008;Nordström et al 2013;Edberg et al 2011). On unmagnetised planets, the ions drift across magnetic field lines on the dayside and the nightside contribution is insignificant (Fränz et al 2015).…”
Section: A23 Cross-field Ion Lossmentioning
confidence: 99%
“…Such ions are common in the magnetospheric tail lobes. Careful investigation of this "problem" has resulted in a new method to detect positive low-energy ions, otherwise invisible to detectors on a sunlit spacecraft positively charged to several volts (Engwall et al, 2006(Engwall et al, , 2009aAndré and Cully, 2012). However, it is not possible to recover the ambient geophysical electric field in such cases.…”
Section: Introductionmentioning
confidence: 99%